Solusi Sengketa Tanah di Era Reformasi Politik dan Desentralisasi Indonesia - Minako Sakai (Antropologi Indonesia, 2002)
This paper will evaluate the impact of some early years of political reforms, democratization and regional autonomy on agrarian matters. During the New Order period, land resources were appropriated without consultation with local communities and land disputes have emerged to the political surface in many regions of Indonesia. The data I present here derive from South Sumatra, one of the hottest areas of Indonesia for disputed land. It will particularly focus on two key issues of agrarian matters, the position of the hak ulayat and solutions of land disputes.